Upaya Meningkatkan Motivasi Belajar Santri Dalam Pembelajaran Kitab Kuning Di Madrasah - Muhamad Syahid Al Qowi; Wawan; Syarief Hasani (THORIQOTUNA: Jurnal Pendidikan Islam, 2024)
The study of classical Islamic texts (kitab kuning) has become a mandatory part of the curriculum in madrasahs. Students are expected to learn these texts to gain a deeper understanding of Islamic knowledge and to facilitate their religious activities. This research aims to describe the process of teaching kitab kuning in madrasahs, the supporting and inhibiting factors in this learning, and efforts to enhance student motivation. The methodology used is qualitative descriptive research through interviews, observations, and documentation. The findings reveal that the learning process in both madrasahs follows a similar curriculum and method, despite slight differences in implementation. Supporting factors include texts with diacritics and translations, as well as teachers’ mastery of the material, while challenges include limited time and student attendance. To enhance motivation, various efforts have been implemented, such as integrating technology with traditional learning, using digital media, interactive teaching methods, group discussions, and contextualizing the curriculum. Ultimately, learning kitab kuning in these madrasahs serves as a foundational step for students wishing to explore Islamic religious knowledge comprehensively in pesantren and other Islamic study centers